FAMILY PSYCHODIDAE - Bejarano, Eduar Elías; Estrada, Luis Gregorio (Zootaxa, 2016)
A catalogue is presented of the species of haematophagous and non-haematophagous psychodids recorded in Colombia. The list comprises 199 species distributed among five subfamilies and 16 genera, as follows: Subfamily Bruchomyiinae, genus Nemopalpus Macquart, 1838 (4 species); subfamily Phlebotominae, genera Brumptomyia França & Parrot, 1921 (8 species), Lutzomyia França, 1924 (153 species) and Warileya Hertig, 1948 (2 species); subfamily Psychodinae, genera Arisemus Satchell, 1955 (3 species), Australopericoma Vaillant, 1975 (1 species), Balbagathis Quate, 1996 (1 species), Clogmia Enderlein, 1937 (1 species), Didicrum Enderlein, 1937 (1 species), Feuerborniella Vaillant, 1971 (1 species), Lepidiella Enderlein, 1937 (1 species), Maruina Müller, 1895 (4 species), Paramormia Enderlein, 1935 (1 species), Parasetomima Duckhouse, 1968 (1 species) and Psychoda Latreille, 1796 (7 species); subfamily Sycoracinae, genus Sycorax Haliday, 1839 (5 species); and subfamily Trichomyiinae, genus Trichomyia Haliday, 1839 (5 species).